"Dancing grannies" in the modern city: consumption and group formation in urban China. Issue 3 (1st September 2016) - Huang, Claudia
Abstract : According to the popular narrative on congregational dancing in Chinese cities, people who participate in dance groups are relics from the collective era who are (1) still motivated by collective ideals, and (2) unwilling or unable to participate in modern consumer culture. This article demonstrates that these are misunderstandings: many dancers actually have embodied consumer logics and participate in congregational dancing in order to practice self-management. However, they continue to be mistaken for vestiges of the past because they cultivate their individualities within collective groups. Building on theories of consumerism, subjectivity, and group formation, I argue in this article that congregational dance groups represent a new form of post-socialist collectivity that exists outside of state-approved social structures.